You did what? : the biggest blunders professionals make - Zoller, Kim; Preston, Kerry (Confident Communicator's Guide., 2015)
"A guide to help business people avoid common faux pas in their contacts with employers, employees, colleagues, clients, and prospects"--Provided by publisher